Construction of new EST-SSRs for Fusarium resistant wheat breeding. (June 2017) - Yumurtaci, Aysen; Sipahi, Hulya; Al-Abdallat, Ayed; Jighly, Abdulqader; Baum, Michael
Graphical abstract: Highlights: "Both in silico mining and molecular validation of wheat EST-SSRs may help to understand the critical genome regions expressed under Fusarium pathogen attack and to provide new candidates for wheat breeding studies". "Especially, wheat chromosome 1B derived two EST-SSRs (contig 556 and contig 1207) exhibited clear separation between Fusarium resistant and susceptible wheat genotypes". D genome derived one EST-SSR (Contig 578) generated a polymorphic 204 bp fragment for FRR resistant cultivars (2–49, Altay2000 and Sunco). Abstract: Surveying Fusarium resistance in wheat with easy applicable molecular markers such as simple sequence repeats (SSRs) is a prerequest for molecular breeding. Expressed sequence tags (ESTs) are one of the main sources for development of new SSR candidates. Therefore, 18.292 publicly available wheat ESTs were mined and genotyping of newly developed 55 EST-SSR derived primer pairs produced clear fragments in ten wheat cultivars carrying different levels of Fusarium resistance. Among the proved markers, 23 polymorphic EST-SSRs were obtained and related alleles were mostly found on B and D genome. Based on the fragment profiling and similarity analysis, a 327 bp amplicon, which was a product of contig 1207 (chromosome 5BL), was detected only in Fusarium head blight (FHB) resistant cultivars (CM82036 and Sumai) and the amino acid sequences showed a similarity to pathogen related proteins. Another FHB resistance related EST-SSR, Contig 556 (chromosome 1BL) produced a 151 bp fragment in Sumai and was associated to wax2-like protein. A polymorphic 204 bp fragment, derived from Contig 578 (chromosome 1DL), was generated from root rot (FRR) resistant cultivars (2–49; Altay2000 and Sunco). A total of 98 alleles were displayed with an average of 1.8 alleles per locus and the polymorphic information content (PIC) ranged from 0.11 to 0.78. Dendrogram tree with two main and five sub-groups were displayed the highest genetic relationship between FRR resistant cultivars (2–49 and Altay2000), FRR sensitive cultivars (Seri82 and Scout66) and FHB resistant cultivars (CM82036 and Sumai). Thus, exploitation of these candidate EST-SSRs may help to genotype other wheat sources for Fusarium resistance.